Optimizing the Cooperation Between Teacher and Parents in the Implementation of Studying From Home for Early Childhood - Nini Aryani; Nopa Wilyanita (AL-ISHLAH: Jurnal Pendidikan, 2021)
Early childhood education is being conducted at home in the event of a Covid-19 pandemic. Parents in the WhatsApp Group receive teaching materials from the teacher via this method of instruction. As a result, teachers and parents must work together to ensure that children at home are still receiving an education that is tailored to their individual needs. This study used a qualitative approach based on interviews with teachers and parents from five Aisyiyah Bustanul Athfal Kindergartens located in Pekanbaru City. In the study, teachers and parents found that a positive attitude in communication patterns between them. They can lead to good patterns of cooperation, with parents being able to guide and motivate their children while implementing learning at home and being directly involved in learning with children by accompanying their children while studying.